New development: Performance promises and pitfalls in hybrid organizations—five challenges for managers and researchers. Issue 6 (19th September 2017) - Skelcher, Chris; Smith, Steven Rathgeb
Abstract : Public and non-profit organizations can contain apparently irreconcilable institutional logics—such as public service and market survival. These logics can hybridize to frame an organization's work and the identity of employees, volunteers and clients in particular ways. These offer both performance promises and performance pitfalls. The authors identify five challenges of hybrid organizations for managers and researchers: measuring performance; innovation; governance; regulation; and sustainability.